SPATIAL ANALYSIS OF SULPHATE AND PHOSPHATE LEVELS OF MAJOR DOMESTIC WATER INTAKE SOURCES IN DUTSIN-MA TOWN, KATSINA STATE, NIGERIA - Ndabula, C.; Jiduana, G. G.; Abaje, I. B.; Adamu, G. K.; Ubogu, A. E.; Ati, O. F.; Odigie, V. A. (FUDMA Journal of Sciences, 2023)
This study aims at determining phosphates and sulphates levels of major domestic water intake sources in Dutsin-Ma town in order to observe some spatial patterns. The field and sampling design gave a target of thirty four (34) samples from open surface, shallow wells, boreholes, and pipe borne evenly distributed among the spatial local administrative units of the town. Gravimetric method was applied in the analysis of Total Dissolved Solids (TDS), while the spectrophotometric method was used analysis of both sulphate and Phosphate. Results of analysis showed that TDS and phosphate have very high levels, while sulphate is lower in most of the domestic water intake sources. The levels of TDS, sulphate and phophate were scaled into a 4-class suitability quality for domestic uses. Based on this classification about 72.00, 72.41 and 6.90% of intake sources fall into the ‘More Unsuitable’ limits for domestic uses for TDS, phoslphate and sulphate respectively. The treated water from Water Board at source shows all these parameters to be at ‘More Suitable” levels for domesticuses. However, result identified possible contamination along distribution pipes as levels at terminal intake points of these pipe showed higher values of these parameters investigated. It is recommended therefore, that the results of the study should be used to develop a framework for domestic water quality surveillance and intervention infrastructure. Pipe borne water supply system should have a routine maintenance. All other sources of domestic water with unsuitable levels of these contaminants should be tagged with precaution notices and the
Keywords: boreholes, open surface, pipe borne, shallow wells, spatial, and surveillance